2022
DOI: 10.1212/nxi.0000000000001183
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning From S1P Receptor Modulators to B Cell–Depleting Therapies in Multiple Sclerosis

Abstract: Background and ObjectivesPatients with multiple sclerosis (MS) transition from oral sphingosine-1-receptor (S1P) modulators to anti-CD20 therapies for several circumstances. Optimal timing of this transition is uncertain, given competing concerns of rebound disease activity and ensuring immune reconstitution. The objective of this study was to evaluate the relationship between inflammatory activity and the transition period from fingolimod to anti-CD20 therapies in a real-world MS cohort.MethodsMedical records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Rowles et al described evolution of patients switching from fingolimod to BCDT with a shorter washout period (median 28 days) and evidenced no relapse within the first 6 months of treatment in patients with a washout period <1 month. 17 We evidenced very similar results in this study in a group of patients with a short washout duration. We also compared here the potential risk of reactivation between fingolimod and another prior DMT.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Rowles et al described evolution of patients switching from fingolimod to BCDT with a shorter washout period (median 28 days) and evidenced no relapse within the first 6 months of treatment in patients with a washout period <1 month. 17 We evidenced very similar results in this study in a group of patients with a short washout duration. We also compared here the potential risk of reactivation between fingolimod and another prior DMT.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies clearly demonstrated that MS disease reactivation is frequent and could be acute after fingolimod withdrawal. 14 - 16 Recent studies specifically assessed the switch from fingolimod to BCDT 4 - 6 , 17 and found a long washout period in patients switching from fingolimod to BCDT associated with risk of relapse. Zhong et al 6 reported a higher risk of relapse within the first 3 months of OCR for patients switching from fingolimod with a mean washout period of 48.5 days than for patients who previously received another DMT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MS is an autoimmune demyelinating and neurodegenerative disease associated with derailments of the innate and adaptive immune system. While its entire immunopathogenesis is not fully clear, current notions posit that T and B cells, macrophages, monocytes, and microglia (endogenous phagocytes of the CNS) are involved, [19][20][21][22][23][24][25][26][27] (Figure 1).…”
Section: Neuropathology and Diagnosis Of Msmentioning
confidence: 99%
“…Rebound activity has been reported following discontinuation of sequestering therapies, such as fingolimod [98][99][100] and natalizumab [101][102][103]. However, rapid switch to an anti-CD20 treatment, such as ocrelizumab, may reduce this rebound risk [104].…”
Section: Hematologic Abnormalitiesmentioning
confidence: 99%